Method for producing recycled positive electrode active material
By employing a heating space with controlled temperature and carbon dioxide gradients, the method addresses the issue of positive electrode active material deterioration during recycling, resulting in effective suppression of degradation and high-quality recycled materials.
Patent Information
- Application Number
- JP2024053998
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2024-03-28
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-03-28
AI Technical Summary
The recycling of positive electrode active materials from battery waste is hindered by the risk of deterioration due to high-temperature carbon dioxide generated during the heating process.
A method involving the use of a heating space with a high temperature region and a low temperature region, where the carbon dioxide concentration is lower in the high temperature region, to minimize contact between high-temperature carbon dioxide and the positive electrode active material.
This method effectively suppresses the deterioration of the positive electrode active material due to high-temperature carbon dioxide, enabling the production of high-quality recycled positive electrode active materials.
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a recycled positive electrode active material. [Background technology]
[0002] The positive electrode active material of a battery contains rare metal components such as cobalt, nickel, manganese, and lithium, and in particular, the positive electrode active material of a non-aqueous electrolyte secondary battery uses a compound mainly composed of the above rare metal components. In order to conserve the resources of rare metal components, a method for reproducing the rare metal components from waste battery materials of secondary batteries is required.
[0003] For example, Patent Document 1 discloses a method for recovering a positive electrode active material by mixing a positive electrode mixture with an activation treatment agent containing an alkali metal compound, heating the mixture to decompose the binder, and removing the decomposition product and the activation treatment agent with water or the like. This method is cost-effective in that it does not use an organic solvent and directly recovers a positive electrode active material from battery waste. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2012-186150 A Summary of the Invention [Problem to be solved by the invention]
[0005] When recycling the positive electrode active material in the positive electrode mixture, the positive electrode mixture is mixed with an activation treatment agent, and the resulting mixture is heated. When the mixture is heated, the carbon-containing material in the mixture (e.g., the binder contained in the positive electrode mixture) is burned, generating carbon dioxide. The generated carbon dioxide is heated to a high temperature in a heating furnace, and it has been found that contact of the high-temperature carbon dioxide with the positive electrode active material in the mixture may cause deterioration of the positive electrode active material.
[0006] Therefore, an object of the present invention is to provide a method for producing a recycled positive electrode active material that can suppress deterioration of the positive electrode active material due to high-temperature carbon dioxide. [Means for solving the problem]
[0007] The present invention includes, for example, the following [1] to
[10] . [1] A method for producing a recycled positive electrode active material, comprising the following steps: (1) A step of mixing a positive electrode mixture containing a positive electrode active material and a carbon-containing material with an activation treatment agent containing one or more alkali metal compounds to obtain a mixture. (2) A step of heating the mixture in a heating space having a high-temperature region and a low-temperature region that is lower in temperature than the high-temperature region, and in which the carbon dioxide concentration in the high-temperature region is lower than the carbon dioxide concentration in the low-temperature region, to obtain a heated mixture. (3) recovering the heated positive electrode active material from the heated mixture; [2] The manufacturing method described in [1], wherein the heating space is a continuous furnace. [3] The manufacturing method described in [1] or [2], wherein in the step (2), air is sent from the high temperature region to the low temperature region in the heating space. [4] The manufacturing method described in [3], wherein in step (2), when the carbon dioxide concentration in the gas fed into the heating space is compared with the carbon dioxide concentration in the gas exhausted from the heating space, the gas exhausted from the heating space has a higher carbon dioxide concentration. [5] The method according to any one of [1] to [4], wherein carbon dioxide is separated or removed in the high temperature region in the step (2). [6] The method according to any one of [1] to [5], wherein in the step (2), the mixture is heated to a temperature equal to or higher than the melting start temperature of the activation treatment agent. [7] The method according to any one of [1] to [6], wherein in the step (2), the mixture is heated to a temperature lower than the melting start temperature of the activation treatment agent. [8] The method according to any one of [1] to [7], wherein the positive electrode active material contains a lithium compound. [9] The method according to any one of [1] to [8], wherein the positive electrode active material comprises a composite oxide containing at least one element selected from the following element group 1 and at least one element selected from the following element group 2: Element group 1: Ni, Co, Mn, Fe, Al, and P Element group 2: Li, Na, K, Ca, Sr, Ba, and Mg
[10] The method according to any one of [1] to [9], wherein the activation treatment agent contains at least one compound selected from the group consisting of potassium compounds and sodium compounds. Effect of the Invention
[0008] According to the present invention, it is possible to provide a method for producing a recycled positive electrode active material that can suppress deterioration of the positive electrode active material due to high-temperature carbon dioxide. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] (Method of manufacturing recycled positive electrode active material) A method for producing a recycled positive electrode active material will be described below.
[0010] A method for producing a recycled positive electrode active material according to one embodiment of the present invention includes the following steps. Step (1): A step of mixing a positive electrode mixture containing a positive electrode active material and a carbon-containing material with an activation treatment agent containing one or more alkali metal compounds to obtain a mixture. Step (2): A step of heating the mixture in a heating space having a high-temperature region and a low-temperature region that is lower in temperature than the high-temperature region, and in which the carbon dioxide concentration in the high-temperature region is lower than the carbon dioxide concentration in the low-temperature region, to obtain a heated mixture. Step (3): A step of recovering the heated positive electrode active material from the heated mixture.
[0011] According to a method for producing a recycled positive electrode active material according to an embodiment, when a mixture of a positive electrode composite and an activation treatment agent is heated, the mixture is heated in a heating space having a high temperature region and a low temperature region, and the carbon dioxide concentration in the high temperature region is lower than the carbon dioxide concentration in the low temperature region. By intentionally making the temperature in the heating space (e.g., in a heating furnace) non-uniform and lowering the carbon dioxide concentration in the high temperature region, the contact between the carbon dioxide in the high temperature region (in other words, high-temperature carbon dioxide) and the positive electrode active material is suppressed. Therefore, according to the present invention, the deterioration of the positive electrode active material due to high-temperature carbon dioxide can be suppressed. However, the mechanism of the present invention is not limited to the above.
[0012] Each step will be described in detail below.
[0013] Pre-process (A): Positive electrode composite preparation process First, a positive electrode mixture containing a positive electrode active material and a carbon-containing material is prepared.
[0014] In the positive electrode mixture, the particles of the positive electrode active material may be bound to each other by a binder. The positive electrode mixture may contain a conductive material and / or an electrolyte in addition to the positive electrode active material and the binder. When the positive electrode mixture contains a conductive material, the particles of the positive electrode active material and the conductive material may be bound to each other by a binder. The electrolyte is a component that originates from the electrolyte of the battery and is impregnated into the positive electrode mixture. The positive electrode mixture may contain a fluorine compound that originates from the binder and / or the electrolyte (e.g., the electrolyte in the electrolyte).
[0015] [Cathode active material] Examples of the positive electrode active material include composite compounds containing one or more of the following elements as constituent elements: lithium, oxygen, fluorine, sodium, magnesium, aluminum, silicon, phosphorus, sulfur, potassium, calcium, titanium, vanadium, chromium, manganese, iron, cobalt, nickel, copper, zinc, gallium, yttrium, niobium, molybdenum, silver, indium, and tungsten.
[0016] The positive electrode active material may consist of only a single compound or may be composed of a plurality of compounds.
[0017] The positive electrode active material preferably contains a composite oxide containing at least one element selected from the following element group 1 and at least one element selected from the following element group 2. Element group 1: Ni, Co, Mn, Fe, Al, and P Element group 2: Li, Na, K, Ca, Sr, Ba, and Mg
[0018] The positive electrode active material preferably contains a compound represented by the following formula (A).
[0019] Li 1+a M 2 b M 1 M T c O 2+d X e (A) However, M 2 represents at least one element selected from the group consisting of Na, K, Ca, Sr, Ba, and Mg, M 1 represents at least one element selected from the group consisting of Ni, Co, Mn, Fe, Al, and P, M T represents at least one element selected from the group consisting of transition metal elements excluding Ni, Co, Mn, and Fe, X represents at least one element selected from the group consisting of non-metal elements excluding O and P, Satisfies -0.4 < a < 1.5, 0 ≤ b < 0.5, 0 ≤ c < 0.5, -0.5 < d < 1.5, and 0 ≤ e < 0.5.
[0020] M Tis preferably at least one element selected from the group consisting of Cu, Ti, Mg, Al, W, Mo, Nb, Zn, Sn, Zr, Ga, V, B, Si, Ca, Sr, Ba, Ge, Cr, Sc, Y, La, Ta, Tc, Ru, Rh, Pd, Ag, Cd, and In. Examples of X include F, S, Cl, Br, I, Se, Te, and N.
[0021] The positive electrode active material preferably contains a composite oxide containing at least Li and Ni.
[0022] In the positive electrode active material, M 1 The molar fraction of Ni in the above range is preferably 0.3 to 0.95.
[0023] The crystal structure of the positive electrode active material (for example, composite oxide) is not particularly limited, but a layered structure is preferred, and a hexagonal or monoclinic crystal structure is more preferred.
[0024] The hexagonal crystal structure is P3, P31, P32, R3, P-3, R-3, P312, P321, P3112, P3121, P3212, P3221, R32, P3m1, P 31m, P3c1, P31c, R3m, R3c, P-31m, P-31c, P-3m1, P-3c1, R-3m, R-3c, P6, P61, P65, P62, P64, P63 , P-6, P6 / m, P63 / m, P622, P6122, P6522, P6222, P6422, P6322, P6mm, P6cc, P63cm, P63mc, P-6m2, P-6c2, P-62m, P-62c, P6 / mmm, P6 / mcc, P63 / mcm, and P63 / mmc.
[0025] The monoclinic crystal structure belongs to any one space group selected from the group consisting of P2, P21, C2, Pm, Pc, Cm, Cc, P2 / m, P21 / m, C2 / m, P2 / c, P21 / c, and C2 / c.
[0026] The crystal structure of the positive electrode active material preferably belongs to the space group R-3m contained in a hexagonal crystal structure, or the space group C2 / m contained in a monoclinic crystal structure.
[0027] The crystal structure of the positive electrode active material can be identified from a powder X-ray diffraction pattern obtained by powder X-ray diffraction measurement using CuKα radiation as a radiation source.
[0028] The particle size of the positive electrode active material in the positive electrode mixture is not particularly limited, but may be about 0.001 to 100 μm. The particle size distribution of the positive electrode active material can be measured using a laser diffraction scattering particle size distribution measuring device (e.g., Mastersizer 2000, manufactured by Malvern Instruments). A volume-based cumulative particle size distribution curve is created from the particle size distribution, and the particle size (D50) value at 50% accumulation from the fine particle side can be regarded as the average particle size of the positive electrode active material.
[0029] There is no particular limitation on the content of the positive electrode active material in the positive electrode mixture.
[0030] [Carbon-containing materials] Examples of the carbon-containing material contained in the positive electrode mixture include a binder, a conductive material (carbon-based conductive material), and an electrolyte. When the positive electrode mixture contains a binder, particles of the positive electrode active material may be bound to each other by the binder in the positive electrode mixture.
[0031] Examples of the binder (binder before activation treatment) include thermoplastic resins, etc. Specific examples include fluororesins such as polyvinylidene fluoride (hereinafter sometimes referred to as "PVdF"), polytetrafluoroethylene (PTFE), tetrafluoroethylene-hexafluoropropylene-vinylidene fluoride copolymers, hexafluoropropylene-vinylidene fluoride copolymers, and tetrafluoroethylene-perfluorovinyl ether copolymers; polyolefin resins such as polyethylene and polypropylene; and styrene-butadiene copolymers (SBR). The binder may be used alone or in combination of two or more kinds.
[0032] The content of the binder in the positive electrode mixture is not particularly limited, but may be in the following ranges relative to 100 parts by mass of the positive electrode active material. The content of the binder may be 0.5 parts by mass or more, 1 part by mass or more, or 2 parts by mass or more. The content of the binder may be 30 parts by mass or less, 10 parts by mass or less, or 5 parts by mass or less. From these viewpoints, the content of the binder may be 0.5 to 30 parts by mass, 1 to 10 parts by mass, 1 to 5 parts by mass, or 2 to 5 parts by mass.
[0033] [Conductive material] Examples of the conductive material include metal-based conductive materials such as metal particles; and carbon-based conductive materials made of carbon materials.
[0034] Specific examples of carbon-based conductive materials include graphite powder, carbon black (eg, acetylene black), and fibrous carbon materials (eg, graphitized carbon fibers and carbon nanotubes).
[0035] The carbon-based conductive material may be a single carbon material, or may be composed of a plurality of carbon materials.
[0036] The specific surface area of the carbon material used as the carbon-based conductive material is 0.1 to 500 m 2 In this case, the conductive material may have a specific surface area of 30 m 2 / g or more, and is made of only carbon-based conductive materials with a specific surface area of 30 m 2 / g or more, and may be carbon black having a specific surface area of 30 m 2 When an activating treatment agent containing an alkali metal compound having an oxidizing power, which will be described later, is used, the rate of oxidation treatment of the carbon-based conductive material can be increased, and even a carbon material having a small specific surface area can be oxidized in some cases.
[0037] The content of the conductive material in the positive electrode mixture is not particularly limited, but may be in the following ranges relative to 100 parts by mass of the positive electrode active material. The content of the conductive material may be 0 parts by mass or more, more than 0 parts by mass, 1 part by mass or more, 3 parts by mass or more, or 5 parts by mass or more. The content of the conductive material may be 50 parts by mass or less, 40 parts by mass or less, 30 parts by mass or less, 20 parts by mass or less, or 10 parts by mass or less. From these viewpoints, the content of the conductive material may be 0 to 50 parts by mass, more than 0 parts by mass and 40 parts by mass or less, 1 to 30 parts by mass, 1 to 10 parts by mass, 3 to 20 parts by mass, or 5 to 10 parts by mass.
[0038] The positive electrode mixture may contain a metal-based conductive material such as metal particles and / or an electrolyte in addition to the positive electrode active material and the carbon-containing material. When the positive electrode mixture contains a binder and a conductive material, the particles of the positive electrode active material and the conductive material may be bound to each other by the binder. The electrolyte is a component that is derived from the electrolyte of the battery and is impregnated into the positive electrode mixture. The positive electrode mixture may contain a fluorine compound derived from the binder and / or the electrolyte (e.g., the electrolyte in the electrolyte).
[0039] [Electrolytes and Solvents] Examples of the electrolyte include LiPF6, LiBF4, LiClO4, LiN(SO2CF3)2, LiN(SO2F)2, LiCF3SO3, etc. The content of the electrolyte contained in the positive electrode mixture is not particularly limited, but may be 0.0005 to 7 mass %.
[0040] The positive electrode mixture may contain a solvent derived from the electrolyte, such as dimethyl carbonate, diethyl carbonate, or ethyl methyl carbonate.
[0041] [Recovery of cathode mixture] The positive electrode mixture can be obtained by separating and recovering the positive electrode mixture layer from a waste positive electrode having a current collector and a positive electrode mixture layer.
[0042] The "scrap positive electrodes" may be positive electrodes recovered from discarded batteries, and waste positive electrodes generated during the manufacturing process of positive electrodes or batteries. The discarded batteries may be used batteries, or unused but non-standard batteries. The waste positive electrodes may be the ends of positive electrodes generated during the manufacturing process of batteries, or non-standard positive electrodes. As the positive electrode composite, waste positive electrode composite not attached to a current collector (waste generated during the manufacturing process of the positive electrode composite) may also be used.
[0043] The waste positive electrode has a current collector which is a metal foil such as aluminum foil or copper foil, and a positive electrode mixture layer provided on the current collector. The positive electrode mixture layer may be provided on one side or both sides of the current collector.
[0044] Examples of a method for separating the positive electrode mixture layer from a waste positive electrode having a current collector and a positive electrode mixture layer include a method for mechanically peeling the positive electrode mixture layer from the current collector (e.g., a method for scraping the positive electrode mixture layer from the current collector), a method for penetrating a solvent into the interface between the current collector and the positive electrode mixture layer to peel the positive electrode mixture layer from the current collector, a method for dissolving the current collector using an alkaline or acidic aqueous solution to separate the positive electrode mixture layer, etc. The method for mechanically peeling the positive electrode mixture layer from the current collector is preferred.
[0045] Previous process (B): Positive electrode mixture cleaning process Next, when the positive electrode mixture contains an electrolyte, it is preferable to bring the prepared positive electrode mixture into contact with an electrolyte washing solvent to remove at least a part of the electrolyte from the positive electrode mixture. Specifically, the positive electrode mixture containing the positive electrode active material, the carbon-containing material, etc. is brought into contact with the electrolyte washing solvent to obtain a slurry containing a solid component and a liquid component, and then the slurry is separated into the solid component and the liquid component.
[0046] Solid-liquid separation is an operation for separating a slurry into a solid component and a liquid component. Examples of the method for solid-liquid separation may be conventionally known methods, such as filtration and centrifugation.
[0047] The electrolyte cleaning solvent is not particularly limited. Examples of the electrolyte cleaning solvent include carbonates such as ethylene carbonate, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, and propylene carbonate; water; ketones such as acetone, methyl ethyl ketone, diethyl ketone, and methyl isobutyl ketone; and alcohols such as ethanol, methanol, propanol, and isopropyl alcohol.
[0048] The positive electrode mixture can be brought into contact with the electrolyte washing solvent in a known contact device for powder and liquid (for example, a stirring tank).
[0049] In the step of contacting the positive electrode mixture with the electrolyte washing solvent, it is preferable to obtain a slurry by stirring the positive electrode mixture and the electrolyte washing solvent. The peripheral speed of the tip of the stirring blade may be 0.1 to 1.0 m / s.
[0050] In the washing step of the positive electrode composite material, after solid-liquid separation, the solid component may be rinsed. The rinsing is an operation in which the solid component is again brought into contact with the electrolyte washing solvent to obtain a slurry, and the slurry is again separated into a solid component and a liquid component. In the washing step of the positive electrode composite material, rinsing may be performed multiple times. The slurry concentration in the rinsing can be adjusted as desired. In the rinsing, the slurry can also be stirred as described above.
[0051] The above-mentioned washing can sufficiently remove the electrolyte from the positive electrode mixture. For example, if the electrolyte remains, the following reaction occurs, and the structure of the positive electrode active material may change from a layered rock salt structure to a spinel structure. LiPF6+16LiMO2+2O2→ 6LiF+Li3PO4+8LiM2O4
[0052] Furthermore, when the activation treatment agent contains lithium carbonate, lithium may be consumed through the following reaction. LiPF6+4Li2CO3→ 6LiF+Li3PO4+4CO2
[0053] The separated solid component may be dried to remove the electrolyte washing solvent by reducing pressure and / or heating, if necessary. The heating temperature may be 50 to 200°C.
[0054] Step (1): Activation treatment agent mixing step Next, the prepared positive electrode mixture and an activation treatment agent containing one or more types of alkaline compounds are mixed to obtain a mixture.
[0055] The method for mixing the positive electrode mixture and the activation treatment agent may be either dry mixing or wet mixing, or a combination of these mixing methods. The order in which the positive electrode mixture and the activation treatment agent are mixed is not particularly limited.
[0056] During mixing, it is preferable to use a mixer equipped with mixing media such as balls and to carry out a pulverizing and mixing step, which can improve the mixing efficiency.
[0057] As a mixing method, dry mixing is preferred because mixing can be performed more easily. In dry mixing, a V-type mixer, a W-type mixer, a ribbon mixer, a drum mixer, a powder mixer equipped with an internal stirring blade, a ball mill, a vibration mill, or a combination of these devices can be used.
[0058] As a mixer used for dry mixing, a powder mixer equipped with an internal stirring blade is preferable, and a specific example thereof is a Loedige Mixer (manufactured by Matsubo Corporation).
[0059] The activation treatment agent used in this step will be described in detail below.
[0060] <Activation treatment agent> The activation treatment agent contains one or more alkali metal compounds. The activation treatment agent preferably contains at least one compound selected from the group consisting of potassium compounds and sodium compounds. Here, potassium and / or sodium may be referred to as alkali metal element X. The activation treatment agent may contain an alkali metal compound containing another alkali metal such as Li in addition to the potassium compound and / or sodium compound.
[0061] When the activation treatment agent comes into contact with the positive electrode active material, the positive electrode active material can be activated. In particular, when the alkali metal compound in the activation treatment agent contains a molten portion, the contact between the molten portion and the positive electrode active material is improved, and the activation of the positive electrode active material is further promoted.
[0062] In addition, the positive electrode mixture may contain a compound containing fluorine derived from the binder and / or the electrolyte, but by contacting the compound containing fluorine with the activation treatment agent, the fluorine component is stabilized as an alkali metal fluoride, so that the generation of corrosive gases such as hydrogen fluoride can be suppressed. Note that it is desirable to prevent the generation of hydrogen fluoride, since it reduces the activity of the positive electrode active material.
[0063] The proportion of all alkali metal compounds in the activation treatment agent is appropriately set taking into consideration the type of alkali metal compound and the type of target positive electrode active material, etc., and is usually 50 mass% or more, preferably 70 mass% or more, relative to the total mass of the activation treatment agent, and may be 100 mass% (an embodiment in which the activation treatment agent is essentially composed of alkali metal compounds).
[0064] The concentration of at least one alkali metal selected from the group consisting of potassium and sodium in the alkali metals contained in the alkali metal compound can be adjusted arbitrarily within the range of 0 to 100 mol%, but is preferably 10 mol% or more, more preferably 20 mol% or more, and is preferably 90 mol% or less, more preferably 80 mol% or less.
[0065] Examples of alkali metal compounds that are components of the activation treatment agent include alkali metal hydroxides, borates, carbonates, oxides, peroxides, superoxides, nitrates, phosphates, sulfates, chlorides, vanadates, bromates, molybdates, and tungstates, etc. These can be used alone or in combination as components of the activation treatment agent.
[0066] Specific examples of suitable alkali metal compounds include hydroxides such as LiOH, NaOH, KOH, RbOH, CsOH, etc.; Borates such as LiBO2, NaBO2, KBO2, RbBO2, CsBO2; Carbonates such as Li2CO3, Na2CO3, K2CO3, RbCO3, CsCO3; Oxides such as Li2O, Na2O, K2O, Rb2O, and Cs2O; Peroxides such as Li2O2, Na2O2, K2O2, Rb2O2, Cs2O2; Superoxides such as LiO2, NaO2, KO2, RbO2, CsO2; Nitrates such as LiNO3, NaNO3, KNO3, RbNO3, CsNO3; Phosphates such as Li3PO4, Na3PO4, K3PO4, Rb3PO4, Cs3PO4; Sulfates such as Li2SO4, Na2SO4, K2SO4, Rb2SO4, Cs2SO4; Chlorides such as LiCl, NaCl, KCl, RbCl, CsCl; Bromides such as LiBr, NaBr, KBr, RbBr, CsBr, etc.; Vanadates such as LiVO3, NaVO3, KVO3, RbVO3, CsVO3; Molybdates such as Li2MoO4, Na2MoO4, K2MoO4, Rb2MoO4, CsMoO4; and Tungstates such as Li2WO4, Na2WO4, K2WO4, Rb2WO4, and CsWO4.
[0067] Here, in order to further enhance the activation effect of the positive electrode active material, the activation treatment agent may contain, in addition to at least one compound selected from the group consisting of potassium compounds and sodium compounds, the same alkali metal element as the alkali metal element contained in the positive electrode active material in the positive electrode mixture.
[0068] That is, when the positive electrode active material in the positive electrode mixture is a lithium composite oxide, the activation treatment agent preferably contains a lithium compound in addition to at least one compound selected from the group consisting of potassium compounds and sodium compounds. Suitable lithium compounds include LiOH, LiBO2, Li2CO3, Li2O, Li2O2, LiO2, LiNO3, Li3PO4, Li2SO4, LiCl, LiVO3, LiBr, Li2MoO4, and Li2WO4.
[0069] The activation treatment agent may contain a compound other than an alkali metal compound as necessary. Examples of the compound other than an alkali metal compound include alkaline earth metal compounds containing alkaline earth metal elements such as magnesium, calcium, barium, etc. The alkaline earth metal compound is contained in the activation treatment agent together with the alkali metal compound for the purpose of controlling the melting start temperature of the activation treatment agent.
[0070] In addition, the content of compounds other than the alkali metal compound in the activation treatment agent is selected within a range that does not significantly suppress the effects derived from the above-mentioned molten alkali metal compound, and can be less than 50 mass% relative to the total mass of the activation treatment agent.
[0071] The amount of the activation treatment agent added in the mixture of the positive electrode mixture and the activation treatment agent is preferably 0.001 to 100 times, and more preferably 0.05 to 1 time, the mass of the positive electrode active material contained in the positive electrode mixture.
[0072] When the activation treatment agent contains a potassium compound and a lithium compound, the ratio of the lithium content (molar) to the potassium content (molar) (lithium content / potassium content) may be 0.01 to 100, 0.1 to 10, or 0.2 to 4, from the viewpoint of making the charge / discharge characteristics of a battery produced using the recycled positive electrode active material more comparable to the charge / discharge characteristics of a battery produced using an unused positive electrode active material.
[0073] When the activation treatment agent contains a sodium compound and a lithium compound, the ratio of the lithium content (molar basis) to the sodium content (molar basis) (lithium content / sodium content) may be 0.01 to 100, 0.1 to 10, or 0.2 to 4, from the viewpoint of making the charge / discharge characteristics of a battery produced using the recycled positive electrode active material more comparable to the charge / discharge characteristics of a battery produced using an unused positive electrode active material.
[0074] When the activation treatment agent contains a potassium compound, the potassium content (molar) contained in the activation treatment agent may be 1% or more and less than 500%, 10% or more and less than 400%, 50% or more and less than 300%, 100% or more and less than 250%, or 150% or more and less than 250% of the fluorine content (molar) contained in the positive electrode composite, from the viewpoint of making the charge / discharge characteristics of a battery manufactured using the recycled positive electrode active material more similar to the charge / discharge characteristics of a battery manufactured using an unused positive electrode active material.
[0075] When the activation treatment agent contains a sodium compound, the sodium content (molar) contained in the activation treatment agent may be 1 to 200%, 10 to 200%, 50 to 200%, or 100 to 200%, 1% or more and less than 150%, 10% or more and less than 150%, 50% or more and less than 150%, or 100% or more and less than 150%, relative to the fluorine content (molar) contained in the positive electrode composite, from the viewpoint of making the charge / discharge characteristics of a battery produced using the recycled positive electrode active material more comparable to the charge / discharge characteristics of a battery produced using an unused positive electrode active material.
[0076] The number of moles of the alkali metal compound in the activation treatment agent in the mixture of the positive electrode composite and the activation treatment agent can be added so that the number of moles of the alkali metal element is 0.001 to 200 times the number of moles of the positive electrode active material (e.g., Formula A) contained in the positive electrode composite.
[0077] By appropriately controlling the ratio of the activation treatment agent in the mixture, the cost of recovering the positive electrode active material from the positive electrode mixture can be reduced, and the oxidative decomposition treatment speed of the carbon-containing material (carbon-based conductive material, binder, etc.) can be increased. In addition, the effect of preventing the generation of corrosive gas in the heating step can be improved, and further the discharge capacity of the battery manufactured using the obtained positive electrode active material can be increased.
[0078] At least one of the alkali metal compounds contained in the activation treatment agent is preferably an alkali metal compound that exhibits alkalinity when dissolved in water. When an activation treatment agent containing such an alkali metal compound is dissolved in pure water, the pH of the solution becomes greater than 7. Hereinafter, such an activation treatment agent may be referred to as an "alkaline activation treatment agent."
[0079] By using an alkaline activation treatment agent, it is possible to further suppress the generation of corrosive gases during the heating process, and therefore it is possible to further increase the discharge capacity of a battery manufactured using the recovered positive electrode active material. In addition, by using an alkaline activation treatment agent, it is possible to increase the treatment speed of carbon-containing materials (carbon-based conductive materials, binders, etc.).
[0080] Examples of the alkali metal compounds that exhibit alkalinity when dissolved in water and are contained in the alkaline activation treatment agent include hydroxides, carbonates, hydrogen carbonates, oxides, peroxides, and superoxides of alkali metals. Specifically, hydroxides such as LiOH, NaOH, KOH, RbOH, and CsOH; carbonates such as Li2CO3, Na2CO3, K2CO3, RbCO3, and CsCO3; hydrogen carbonates such as LiHCO3, NaHCO3, KHCO3, RbHCO3, and CsHCO3; oxides such as Li2O, Na2O, K2O, Rb2O, and Cs2O; peroxides such as Li2O2, Na2O2, K2O2, Rb2O2, and Cs2O2; and superoxides such as LiO2, NaO2, KO2, RbO2, and CsO2. One or more of these may be contained in the activation treatment agent.
[0081] In addition, when the conductive material contained in the positive electrode composite is a carbon-based conductive material, at least one of the alkali metal compounds contained in the activation treatment agent may be an alkali metal compound having an oxidizing power that oxidizes and decomposes the carbon-based conductive material at the temperature of the heating step. Hereinafter, an activation treatment agent containing such an alkali metal compound may be referred to as an "activation treatment agent having an oxidizing power."
[0082] Use of an activation treatment agent having such oxidizing power is particularly effective in promoting the oxidation of the conductive material, which is a carbon material, to carbon dioxide, and promoting the oxidation of the binder, which is a hydrocarbon material, to carbon dioxide and water vapor, and can further increase the discharge capacity of a battery manufactured using the obtained positive electrode active material, and can also improve the effect of preventing the generation of corrosive gases during the heating process.
[0083] Examples of alkali metal compounds having the oxidizing power required to oxidize carbonaceous conductive materials and hydrocarbons to carbon dioxide and water vapor include alkali metal peroxides, superoxides, nitrates, sulfates, vanadates, and molybdates, which may be used alone or in combination of two or more.
[0084] Specific examples include superoxides such as Li2O2, Na2O2, K2O2, Rb2O2, and Cs2O2; LiO2, NaO2, KO2, RbO2, and CsO2; nitrates such as LiNO3, NaNO3, KNO3, RbNO3, and CsNO3; sulfates such as Li2SO4, Na2SO4, K2SO4, Rb2SO4, and Cs2SO4; vanadates such as LiVO3, NaVO3, KVO3, RbVO3, and CsVO3; and molybdates such as Li2MoO4, Na2MoO4, K2MoO4, Rb2MoO4, and CsMoO4.
[0085] Details of the oxidizing power of these alkali metal compounds are described in JP 2012-186150 A.
[0086] The alkali metal compound may be a carbonate or sulfate, or at least one selected from the group consisting of Li2CO3, Na2SO4, Na2CO3, and K2CO3, from the viewpoint of making it easier to make the charge / discharge characteristics of a battery produced using the recycled positive electrode active material more comparable to those of a battery produced using an unused positive electrode active material.
[0087] Process (2): Heating process Step (2) (heating step) is a step of heating the mixture obtained in step (1) (hereinafter sometimes referred to as "mixture before heating") in a heating space having a high temperature region and a low temperature region that is lower than the high temperature region, and in which the carbon dioxide concentration in the high temperature region is lower than the carbon dioxide concentration in the low temperature region, to obtain a mixture after heating. By intentionally making the temperature in the heating space (e.g., in a heating furnace) non-uniform and lowering the carbon dioxide concentration in the high temperature region, contact between the carbon dioxide in the high temperature region (in other words, high-temperature carbon dioxide) and the positive electrode active material is suppressed, and therefore deterioration of the positive electrode active material due to high-temperature carbon dioxide can be suppressed.
[0088] The mixture before heating may be heated to a temperature equal to or higher than the melting initiation temperature (Tmp) of the activation treatment agent, or may be heated to a temperature lower than the melting initiation temperature (Tmp) of the activation treatment agent.
[0089] "Melting start temperature (Tmp) of the activation treatment agent" means the lowest temperature at which a part of the activation treatment agent exhibits a liquid phase. The melting start temperature of the activation treatment agent is a value determined by differential thermal analysis (DTA). That is, when 5 mg of the mixture before heating is subjected to differential thermal analysis (DTA, measurement conditions: heating rate: 10°C / min), the melting start temperature is the temperature at which the DTA signal shows an endothermic peak.
[0090] The melting start temperature of the activation treatment agent is preferably 700° C. or lower, and more preferably 600° C. or lower. There is no lower limit to the melting start temperature of the activation treatment agent, but it may be, for example, 150° C. or higher.
[0091] The melting point of the activation treatment agent means the lowest temperature at which a part of the activation treatment agent becomes liquid when the activation treatment agent alone is heated. By mixing the positive electrode composite material and the activation treatment agent, the melting start temperature of the activation treatment agent becomes lower than the melting point of the activation treatment agent.
[0092] The melting point of the activation treatment agent is a value determined by differential thermal analysis (DTA). Specifically, 5 mg of the activation treatment agent is subjected to differential thermal analysis (DTA, measurement conditions: heating rate: 10°C / min), and the temperature at which the DTA signal shows an endothermic peak is taken as the melting point of the activation treatment agent. For example, it may be 50 to 1000°C.
[0093] Examples of the heating space include gas furnaces, electric furnaces, infrared heating furnaces, plasma heat treatment furnaces, heavy oil furnaces, light oil furnaces, hydrogen heat treatment furnaces, induction heating furnaces, vacuum furnaces, salt bath furnaces, tunnel furnaces, roller hearth kiln furnaces, rotary furnaces, walking beam furnaces, carbot furnaces, mesh belt furnaces, rotary kiln furnaces, shuttle kiln furnaces, and fluidized bed sintering furnaces. The heating space is a space in which the mixture to be heated is accommodated, and may be a closed space or an open space having an opening for carrying in or out the mixture. The heating space may be a batch furnace, a continuous furnace, or a fluidized furnace. For example, the rotary kiln furnace may be a batch type rotary kiln furnace or a continuous type rotary kiln furnace. When the heating space is a continuous furnace, the heating space may be a gas furnace, an electric furnace, an infrared heating furnace, a plasma heat treatment furnace, a heavy oil furnace, a light oil furnace, a hydrogen heat treatment furnace, an induction heating furnace, a walking beam furnace, a mesh belt furnace, a continuous rotary kiln furnace, or a continuous shuttle kiln furnace. The fluidized bed sintering furnace may be multi-stage, and the temperature may be changed in each stage.
[0094] The heating space has a high temperature region and a low temperature region that is lower in temperature than the high temperature region. That is, the temperature is non-uniform in the heating space. The temperature distribution in the heating space can be adjusted to a desired temperature distribution by adjusting the position of the heat source in the heating space, the number of heat sources, the output of the heat source, etc. For example, when the heating space is a batch furnace, the temperature in the batch furnace may change depending on the distance from the heat source in the batch furnace. For example, when the heating space is a continuous furnace, the temperature in the continuous furnace may change along the direction of movement of the mixture, or the temperature in the continuous furnace may gradually increase along the direction of movement of the mixture.
[0095] When the heating space is a continuous furnace, the continuous furnace may have, for example, a low-temperature region that is relatively low temperature in the continuous furnace and is present near the inlet, a temperature-raising region in which the temperature gradually increases from the low-temperature region toward the outlet, a constant-temperature region in which the temperature is approximately constant, and a temperature-reducing region in which the temperature gradually decreases from the constant-temperature region toward the outlet, or the constant-temperature region in the continuous furnace may be the high-temperature region. The temperature of each region and the volume of the space occupied by each region in the continuous furnace can be appropriately determined depending on the structure of the continuous furnace, the amount of the mixture before heating, the amount of carbon dioxide generated in the continuous furnace, etc.
[0096] The residence time of the mixture in the heating space (the time from the moment the mixture enters the heating space to the moment the mixture is discharged from the heating space) may be determined according to the temperature in the heating space, the amount of the mixture before heating, etc. The residence time of the mixture may be, for example, 10 minutes to 24 hours.
[0097] The carbon dioxide concentration in a specific region in the heating space can be adjusted, for example, by supplying air in the heating space. Specifically, the carbon dioxide concentration in the high temperature region can be made lower than the carbon dioxide concentration in the low temperature region by supplying air from the high temperature region to the low temperature region in the heating space. Air may be supplied into the heating space only in the direction from the high temperature region to the low temperature region in the heating space, or in other directions.
[0098] The air supply in the heating space may be performed in the entire heating space or in only a part of the heating space. For example, the air supply in the heating space may be performed only in the low temperature region, only in the high temperature region, or in both the low temperature region and the high temperature region.
[0099] In order to increase the exhaust efficiency of carbon dioxide and further suppress the deterioration of the positive electrode active material due to high-temperature carbon dioxide, the air may be sent into the heating space in a temperature range where the amount of carbon dioxide generated in the heating space is large. For example, the air may be sent into the heating space in a range where the temperature is 300 to 900° C., 300 to 700° C., or 300 to 600° C. The air is preferably sent into the continuous furnace in a range where the temperature is lower than the melting start temperature of the activation treatment agent.
[0100] When air is supplied into the heating space, the heating space may have an air supply port for supplying air. The heating space may also have an exhaust port for exhausting carbon dioxide and the like. The heating space may have a plurality of air supply ports or a plurality of exhaust ports.
[0101] When the heating space has an air inlet and / or an exhaust port, the location of the air inlet and / or the exhaust port in the heating space may be determined according to the structure of the heating space, the amount of the mixture before heating, the components contained in the gas to be supplied, the amount of carbon dioxide generated in the heating space, etc. The heating space may have an air inlet (multiple air inlets if there are multiple air inlets) arranged along the bottom surface of the heating space and an exhaust port (multiple exhaust ports if there are multiple exhaust ports) arranged along the top surface of the heating space, an exhaust port (multiple exhaust ports if there are multiple exhaust ports) arranged along the bottom surface of the heating space and an air inlet (multiple air inlets if there are multiple air inlets) arranged along the top surface of the heating space, or an air inlet and an exhaust port (multiple air inlets and multiple exhaust ports if there are multiple air inlets and multiple exhaust ports) arranged along the side surface of the heating space. The air inlet may be arranged to face the exhaust port, or may be arranged not to face the exhaust port.
[0102] When the heating space is a continuous furnace, the air may be fed in a direction perpendicular to the direction of movement of the mixture. In this case, since the direction of movement of the mixture is generally along the bottom, top, or side of the continuous furnace, the air is fed in the continuous furnace in a direction perpendicular to the bottom, top, or side of the continuous furnace. By feeding the air in a direction perpendicular to the direction of movement of the mixture, it is possible to prevent carbon dioxide from stagnation in the continuous furnace, and therefore it is possible to suppress the concentration of carbon dioxide in the continuous furnace from becoming too high. In addition, it is possible to prevent carbon dioxide from stagnation in the continuous furnace, and therefore it is possible to suppress the carbon dioxide from continuing to be heated in the continuous furnace and becoming hot. For these reasons, by feeding the air in a direction perpendicular to the direction of movement of the mixture, it is possible to further suppress the deterioration of the positive electrode active material due to high-temperature carbon dioxide.
[0103] When the heating space is a continuous furnace, the air may be sent in the opposite direction to the direction of movement of the mixture. In this case, since the direction of movement of the mixture is generally along the bottom, top, or side of the continuous furnace, the air is sent in the direction perpendicular to the bottom, top, or side of the continuous furnace. By sending the air in the direction perpendicular to the direction of movement of the mixture, it is possible to prevent carbon dioxide from stagnation in the continuous furnace, and therefore it is possible to suppress the concentration of carbon dioxide in the continuous furnace from becoming too high. In addition, it is possible to prevent carbon dioxide from stagnation in the continuous furnace, and therefore it is possible to suppress the carbon dioxide from continuing to be heated in the continuous furnace and becoming hot. For these reasons, by sending the air in the opposite direction to the direction of movement of the mixture, it is possible to further suppress the deterioration of the positive electrode active material due to high-temperature carbon dioxide.
[0104] The gas sent into the heating space is not particularly limited, and may be, for example, an oxygen-containing gas such as air, or an inert gas such as nitrogen or argon. The gas sent into the heating space is exhausted together with the carbon dioxide generated in the heating space, so that the carbon dioxide concentration in the gas exhausted from the heating space is higher than the carbon dioxide concentration in the gas sent into the heating space. The gas exhausted from the heating space may be sent into the heating space again after removing carbon dioxide.
[0105] The flow rate of the gas per 1 L of the heating space sent into the heating space may be, for example, 0.001 to 1.0 L / min or 0.01 to 0.6 L / min. The flow rate of the gas per 1 L of the heating space may be appropriately adjusted depending on the structure of the heating space, the amount of the mixture before heating, the components contained in the sent gas, the amount of carbon dioxide generated in the heating space, and the like. For example, the flow rate of the gas per 1 L of the heating space may be adjusted to be large from the viewpoint of further suppressing the deterioration of the positive electrode active material by lowering the concentration of carbon dioxide in the continuous furnace, and the flow rate of the gas per 1 L of the heating space may be adjusted to be small from the viewpoint of increasing energy efficiency by suppressing the temperature drop in the heating space contents due to the sending of air. In addition, the flow rate of the gas per 1 L of the heating space may be adjusted to an amount such that the carbon dioxide concentration per 1 L of the heating space is a specific value or less (for example, 10 volume % or less). The flow rate of the gas per 1 L of the heating space sent into the continuous furnace may be approximately the same throughout the continuous furnace, or may be different at each point of the continuous furnace.
[0106] The carbon dioxide concentration in a specific region in the heating space can be adjusted, for example, by a means capable of separating or removing carbon dioxide. That is, carbon dioxide may be separated or removed in the high temperature region so that the carbon dioxide concentration in the high temperature region is lower than the carbon dioxide concentration in the low temperature region. Examples of the means capable of separating or removing carbon dioxide include a carbon dioxide adsorbent, a carbon dioxide absorbent, a carbon dioxide separation membrane, or other device for separating or removing carbon dioxide.
[0107] The ratio of the carbon dioxide concentration in the low temperature region to the carbon dioxide concentration in the high temperature region (carbon dioxide concentration in the low temperature region / carbon dioxide concentration in the high temperature region) is greater than 1. From the viewpoint of further suppressing deterioration of the positive electrode active material due to high-temperature carbon dioxide, the ratio of the carbon dioxide concentration in the low temperature region to the carbon dioxide concentration in the high temperature region may be 1.2 or more, 1.5 or more, 2 or more, 3 or more, 4 or more, or 5 or more.
[0108] The temperature in the heating space (the temperature at any position in the heating space) may be, for example, within the range of room temperature to 2000° C. The temperature of the low temperature region may be lower than the temperature of the high temperature region, for example, room temperature to 300° C. The temperature of the high temperature region may be higher than the temperature of the low temperature region, for example, more than 300° C. and not more than 1000° C.
[0109] The maximum temperature in the heating space (the maximum temperature among the temperatures at any position in the heating space) may be, for example, equal to or higher than the melting start temperature of the activation treatment agent. The maximum temperature in the heating space (the maximum temperature at any position in the heating space) may be, for example, 300 to 1000°C, 350 to 900°C, or 400 to 800°C. The maximum temperature in the heating space may be the same as the maximum temperature in the high temperature region in the heating space.
[0110] In step (2), the mixture before heating is heated to a temperature equal to or higher than the melting temperature of the activation treatment agent, which produces the following effects. That is, the activation treatment agent in a molten state comes into contact with the positive electrode active material, thereby suppressing deterioration of the crystal structure of the positive electrode active material. In addition, the activation treatment agent can also restore the crystal structure.
[0111] When the molten activation treatment agent comes into contact with a carbon-containing material (such as a carbon-based conductive material or binder), the rate of oxidative decomposition of the conductive material and the binder is increased. Furthermore, when the molten activation treatment agent comes into contact with a fluorine compound derived from the binder and the electrolyte, the fluorine component is stabilized as an alkali metal fluoride, preventing the generation of hydrogen fluoride, which is a corrosive gas, and suppressing deterioration of the crystal structure of the positive electrode active material.
[0112] Furthermore, when the activation treatment agent contains the same alkali metal as the positive electrode active material, it is also possible to supply the alkali metal that is insufficient for the positive electrode active material.
[0113] The maximum temperature in the heating space (the maximum temperature at any position in the heating space) is preferably higher than the melting point of the alkali metal compound contained in the activation treatment agent. The melting point of the alkali metal compound may be lower than the melting point of each alkali metal compound alone by mixing two or more types of alkali metal compounds, and when the activation treatment agent contains two or more types of alkali metal compounds, the eutectic point is taken as the melting point of the alkali metal compound.
[0114] The time for which the mixture is heated to the melting initiation temperature of the activation treatment agent or higher may be determined depending on the amount of the mixture before heating, etc. The time for which the mixture is heated to the melting initiation temperature of the activation treatment agent or higher may be, for example, 1 minute to 24 hours.
[0115] The maximum temperature in the heating furnace (the maximum temperature among the temperatures at any position in the heating furnace) may be, for example, not higher than the melting temperature of the activation treatment agent. The maximum temperature in the heating furnace (the maximum temperature at any position in the heating furnace) may be, for example, 300 to 600°C, 350 to 575°C, or 400 to 550°C.
[0116] In step (2), the mixture before heating is heated to a temperature below the melting start temperature of the activation treatment agent, thereby suppressing deterioration of the crystal structure of the positive electrode active material due to heating at high temperatures, and making it easier to achieve charge / discharge characteristics equivalent to those of a battery manufactured using an unused positive electrode active material. In addition, the crystal structure can be restored by heating the mixture before heating together with the activation treatment agent. In this specification, "heating to a temperature below the melting start temperature of the activation treatment agent" means heating while maintaining a temperature below the melting start temperature of the activation treatment agent (heating at a holding temperature below the melting start temperature of the activation treatment agent). In addition, "heating to a temperature below the melting start temperature of the activation treatment agent" means not heating at a temperature equal to or higher than the melting start temperature of the activation treatment agent.
[0117] When the heated activation treatment agent comes into contact with a carbon-containing material (such as a carbon-based conductive material or binder), the rate of oxidative decomposition of the conductive material and the binder is increased. Furthermore, when the heated activation treatment agent comes into contact with a fluorine compound derived from the binder and the electrolyte, the fluorine component is stabilized as an alkali metal fluoride, preventing the generation of hydrogen fluoride, which is a corrosive gas, and suppressing deterioration of the crystal structure of the positive electrode active material.
[0118] The time for which the mixture is heated at a temperature lower than the melting initiation temperature of the activation treatment agent may be determined depending on the amount of the mixture before heating, etc. The time for which the mixture is heated at a temperature lower than the melting initiation temperature of the activation treatment agent may be, for example, 1 minute to 24 hours.
[0119] After the heating step, the mixture can be cooled to any temperature, such as about room temperature, as necessary. In this manner, a heated mixture containing a heated positive electrode active material is obtained.
[0120] Step (3): Positive electrode active material recovery step The positive electrode active material recovery step is a step of recovering the heated positive electrode active material from the heated mixture after the heating step (2).
[0121] The mixture after heating contains, in addition to the heated positive electrode active material, components derived from the activation treatment agent (alkali metal compounds, etc.), undecomposed carbon-containing materials (carbon-based conductive materials, binders, etc.), and other undecomposed substances of the positive electrode mixture. In addition, when the positive electrode mixture contains an electrolyte solution containing a fluorine component, the mixture may contain a fluorine component derived from the electrolyte.
[0122] Examples of methods for separating and recovering the heated positive electrode active material from the heated mixture include a solid-liquid separation method in which a solvent such as water is added to the mixture to form a slurry, followed by solid-liquid separation, and a vaporization separation method in which the mixture is heated to vaporize and separate components other than the heated positive electrode active material. The solid-liquid separation method will be described below.
[0123] Step (3a): Solid-liquid separation step Step (3a) is a step of contacting the heated mixture with a liquid containing water to obtain a slurry containing a solid component and a liquid component, and then separating the slurry into the solid component and the liquid component.
[0124] The mixture after heating contains, in addition to the heated positive electrode active material, components derived from the activation treatment agent (alkali metal compounds, etc.), undecomposed carbon-containing materials (carbon-based conductive materials, binders, etc.), and other undecomposed substances of the positive electrode composite. In addition, when the positive electrode composite contains an electrolyte solution containing a fluorine component, the mixture may contain a fluorine component derived from the electrolyte.
[0125] In order to separate and recover the heated positive electrode active material from the heated mixture, a liquid containing water (liquid) is added to the mixture to form a slurry, which is then subjected to solid-liquid separation to separate the solid component and the liquid component.
[0126] The liquid used in the slurrying step is not particularly limited as long as it contains water. The amount of water in the liquid may be 50% by mass or more. In order to increase the solubility of water-soluble components or to increase the processing speed, components other than water may be added to the liquid to adjust the pH. Suitable examples of the liquid containing water include pure water and alkaline cleaning liquid. Examples of the alkaline cleaning liquid include an aqueous solution of at least one anhydride selected from the group consisting of lithium hydroxide, sodium hydroxide, potassium hydroxide, lithium carbonate, sodium carbonate, potassium carbonate, and ammonium carbonate, and a hydrate thereof. Ammonia can also be used as the alkali.
[0127] The resulting slurry contains a solid component mainly containing the positive electrode active material after heating and a liquid component containing water-soluble components other than the positive electrode active material. The liquid component contains an alkali metal component derived from the activation treatment agent and / or a fluorine component derived from the binder and the electrolyte.
[0128] The amount of liquid to be added to the mixture is appropriately determined taking into consideration the amounts of the post-heating positive electrode active material and water-soluble components other than the positive electrode active material contained in the mixture.
[0129] In step (3a), it is preferable to obtain a slurry by stirring the mixture after heating with a liquid containing water. This promotes dissolution of the water-soluble components. The peripheral speed of the tip of the stirring blade is preferably 0.1 to 0.9 m / s.
[0130] The slurry formed in the slurrying step is then subjected to solid-liquid separation. Solid-liquid separation is a step of separating the slurry into a liquid component and a solid component. The method of solid-liquid separation may be a conventional method, such as filtration or centrifugation.
[0131] In step (3a), after the solid-liquid separation, the obtained solid component may be rinsed. Rinsing is an operation in which the obtained solid component is contacted again with a liquid containing water to obtain a slurry, and then the slurry is separated again into a solid component and a liquid component. In step (3a), rinsing may be performed multiple times. The slurry concentration in the rinse may be the same as above.
[0132] In this specification, the positive electrode active material that has undergone steps (1) to (3) is called a recycled positive electrode active material. The recycled positive electrode active material that has undergone steps (1) to (3) can be suitably used for manufacturing a positive electrode or the like. The manufacturing method of the recycled positive electrode active material may include additional steps before and after steps (1) to (3). In this specification, the positive electrode active material that has undergone additional steps other than steps (1) to (3) is also called a recycled positive electrode active material. Examples of the additional steps other than steps (1) to (3) are pre-step (A) and pre-step (B) that are performed before step (1), and the following steps (4) and (5) that are performed after step (3), for example, after step (3a).
[0133] Process (4): Drying process Step (4) is, for example, a step of removing water from the solid component obtained in step (3a) by exposing the solid component to a heating and / or reduced pressure environment.
[0134] The heating temperature is preferably 100°C or higher to remove water. It is more preferably 150°C or higher to remove water sufficiently. In particular, a temperature of 250°C or higher is preferable because the discharge capacity of a battery manufactured using the obtained positive electrode active material is further increased. The temperature in the drying step may be constant, or may be changed stepwise or continuously. The heating temperature range may be, for example, 10°C or higher and less than 900°C.
[0135] The ultimate pressure range of the reduced pressure is, for example, 1.0×10 -10 ~1.0×10 3 It can be Pa.
[0136] Step (5): Annealing (re-firing) step Step (5) may be a step of heat treating the solid component obtained after step (4) at less than 900° C. when the activation treatment agent is heated to a temperature equal to or higher than the melting initiation temperature.
[0137] Step (5) may be a step of heating the solid component after step (4) at a temperature higher than that of step (2) when the activation treatment agent is heated at a temperature lower than the melting initiation temperature. In this case, the temperature at which the mixture after heating is heated may be more than 700° C., 750° C. or higher, 800° C. or higher, 850° C. or higher, or 900° C. or higher, from the viewpoint of vaporizing components other than the positive electrode active material and removing impurities, and from the viewpoint of making it easier to achieve charge / discharge characteristics equivalent to those of a battery manufactured using an unused positive electrode active material by sufficiently increasing the crystallite size of the positive electrode active material.
[0138] The atmosphere for the heat treatment is not limited, but an oxygen-containing atmosphere such as air is preferable. The heat treatment temperature can be 100°C or higher. The heat treatment holding time can be 1 minute to 24 hours. It is particularly preferable to heat at a holding temperature of 350°C or higher for 0.1 to 5 hours.
[0139] The recycled positive electrode active material obtained from the battery mixture by using the method for producing the recycled positive electrode active material of the present invention can be reused in the same way as unused active material. Methods for producing positive electrodes and batteries using recycled positive electrode active materials are well known.
[0140] The final discharge capacity of the recycled positive electrode active material according to the embodiment of the present invention can be 150 mAh / g or more. EXAMPLES
[0141] The present invention will be described in more detail below with reference to examples. However, the present invention is not limited to the following examples unless the gist of the present invention is changed.
[0142] Measurement of the physical properties of the positive electrode active material and the recycled positive electrode active material, and a charge / discharge test using a battery using the positive electrode active material were carried out as follows.
[0143] [Element content] The content of alkali metal elements in the solution and the powder was analyzed using an ICP emission spectrometer (e.g., SPS3000 manufactured by SII NanoTechnology Inc.) for the solution and the acid solution in which the powder was dissolved.
[0144] (Reference example 1) <Production of positive electrodes> The positive electrode described below was prepared by the following procedure. A mixture was obtained by mixing 92 parts by mass of a positive electrode active material (unused positive electrode active material or recycled positive electrode active material), 3 parts by mass of PVdF (binder, manufactured by Kureha Corporation, product number: #1100), and 5 parts by mass of acetylene black (conductive material, manufactured by Denka Co., Ltd., product number: HS100). As the binder PVdF, a binder solution in which PVdF was dissolved in NMP in advance was used. The mixture was kneaded with a rotation-revolution type mixer (ARE-310 manufactured by Thinky Corporation) to prepare a positive electrode mixture paste. NMP was added to adjust the total mass of the positive electrode active material, binder, and conductive material in the positive electrode mixture paste to 50% by mass.
[0145] A 20-μm-thick aluminum foil 1085 (manufactured by Nippon Foil Co., Ltd.) for use as a positive electrode current collector for lithium-ion secondary batteries was attached to one side of the foil in an amount of 3.0 ± 0.1 mg / cm2. 2 The positive electrode composite paste was applied so that the positive electrode was formed as follows: After that, it was vacuum dried at 150°C for 8 hours to obtain a positive electrode. The electrode area of this positive electrode was 1.65 cm 2 It was decided.
[0146] <Battery manufacturing> The coin-type battery described below was produced by the following procedure. The above-mentioned positive electrode, electrolyte, separator, and negative electrode were combined to produce a nonaqueous electrolyte secondary battery (coin-type battery). The battery was assembled in a glove box in an argon atmosphere. As the electrolyte, a solution in which LiPF6 was dissolved at a ratio of 1.0 mol / L in a 30:35:35 (volume ratio) mixture of ethylene carbonate, dimethyl carbonate, and ethyl methyl carbonate was used. As the separator, a laminated film separator in which a heat-resistant porous layer was laminated on a porous film (made of polyethylene) was used, and metallic lithium was used as the negative electrode.
[0147] <Production of positive electrodes before recycling> The positive electrode active material is Li 1.07 Ni 0.47 Mn 0.48 Fe 0.05 A positive electrode active material having a crystal structure of R-3m and a molecular weight of 02 was prepared. The above-mentioned coin-type battery was produced using this positive electrode active material (unused positive electrode active material), and the following charge-discharge test (rate test) was carried out while maintaining the temperature at 25°C. The 0.2C discharge capacity was 138mAh / g, and the 5C discharge capacity was 106mAh / g. The larger the 0.2C discharge capacity, the higher the rated capacity obtained, and the larger the 5C discharge capacity, the higher the output characteristics obtained. (conditions) Maximum charging voltage: 4.3V Charging current: 0.2mA / cm 2 Charging time: 8 hours Minimum discharge voltage: 2.5V 0.2C discharge current: 0.2mA / cm 2 5C discharge current: 5.0mA / cm 2
[0148] The electrode mixture was mechanically scraped off from the positive electrode used in the above battery, and the electrode mixture was peeled off from the current collector. 5 g of the electrode mixture removed from the positive electrode was mixed with 0.1 mol of K2CO3 per 1 mol of positive electrode active material and 0.1 mol of Na2CO3 per 1 mol of positive electrode active material as an activation treatment agent to obtain a mixture (mixture before heating). The melting start temperature of the activation treatment agent was 700°C.
[0149] The mixture before heating was placed in an electric furnace and heated in an air atmosphere at a heating temperature of 700° C. (above the melting start temperature of the activation treatment agent) for a heating time of 240 minutes.
[0150] The mixture after heating was pulverized, and distilled water was added and stirred to obtain a slurry. The obtained slurry was filtered to separate a solid component and a liquid component. The solid component was then collected and dried to obtain a recycled positive electrode active material. The composition, crystal structure, average particle size, and specific surface area of the obtained recycled positive electrode active material were comparable to those of an unused positive electrode active material. The above coin-type battery was produced using the recycled positive electrode active material, and a charge / discharge test was performed under the above conditions while maintaining the temperature at 25°C. The 0.2C discharge capacity was 135mAh / g, and the 5C discharge capacity was 94mAh / g, which was comparable to the discharge capacity of a coin-type battery produced using an unused positive electrode active material.
[0151] (Reference example 2) <Production of positive electrodes before recycling> The positive electrode active material is LiNi 0.33 Co 0.33 Mn 0.33A positive electrode active material NCM111 having a crystal structure of R-3m was prepared. When the above coin-type battery was produced using this positive electrode active material (unused positive electrode active material), the initial charge capacity was 178.3mAh / g and the initial discharge capacity (0.2C) was 163.4mAh / g. In addition, when the following charge / discharge test (rate test) was performed while maintaining the temperature at 25°C, the 0.2C discharge capacity was 163.1mAh / g and the 5C discharge capacity was 141.3mAh / g.
[0152] The electrode mixture was mechanically scraped off from the cathode of the process waste material generated during the preparation of the above cathode, and the electrode mixture was peeled off from the current collector. 5 g of the electrode mixture removed from the cathode was mixed with 0.1 mol of Li2CO3 per 1 mol of the cathode active material and 0.1 mol of Na2SO4 per 1 mol of the cathode active material as activation treatment agents to obtain a mixture (mixture before heating). The melting start temperature of the activation treatment agent was 510°C.
[0153] 30 g of the mixture before heating was placed in an electric furnace and heated in an air atmosphere at a heating rate of 300° C. / h, a heating temperature of 450° C. (lower than the melting start temperature of the activation treatment agent), and a heating time of 360 minutes.
[0154] The mixture after heating was pulverized, and distilled water was added and stirred to obtain a slurry. The obtained slurry was filtered to separate a solid component and a liquid component. The solid component was then collected and dried by suction at 100°C for 1 hour.
[0155] The solid component after drying was placed in an electric furnace, and heated in an air atmosphere at a heating temperature of 900°C for 60 minutes to obtain a recycled positive electrode active material after heating. Next, the recycled positive electrode active material after heating was naturally cooled to room temperature, and it was confirmed that the composition, crystal structure, average particle size, and specific surface area of the obtained recycled positive electrode active material were comparable to those of an unused positive electrode active material. When the above coin-type battery was produced using the recycled positive electrode active material, the initial charge capacity was 180.5mAh / g and the initial discharge capacity was 161.1mAh / g. In addition, when the initial charge / discharge (rate test) was performed under the above conditions while maintaining at 25°C, the 0.2C discharge capacity was 160.2mAh / g and the 5C discharge capacity was 133.9mAh / g.
[0156] Example 1 The electrode mixture is mechanically scraped off from the positive electrode prepared above, and the electrode mixture is peeled off from the current collector. 5 g of the electrode mixture removed from the positive electrode is mixed with 0.1 mol and 0.1 mol of K2CO3 and Li2CO3 as activation treatment agents per 1 mol of the positive electrode active material in the electrode mixture to obtain a mixture (mixture before heating).
[0157] The mixture before heating is carried into a continuous furnace. The continuous furnace is provided with an air inlet on the discharge side of the mixture, and an exhaust port on the inlet side of the mixture. The mixture is heated to a temperature above the melting start temperature (700°C) of the activation treatment agent while air is fed from the air inlet to the exhaust port in the opposite direction to the direction of movement of the mixture in the continuous furnace. At this time, a temperature distribution is generated in the continuous furnace such that the temperature gradually increases from the inlet to the outlet, and the carbon dioxide concentration in the high temperature region of 400 to 750°C is lower than the carbon dioxide concentration in the low temperature region of 25 to 400°C due to the air feeding. The heating in the series of continuous furnaces is temperature controlled, with the maximum temperature of the continuous furnace at 750°C, the residence time being 24 hours, and the time for heating at a temperature above the melting start temperature (700°C) of the activation treatment agent being 5 hours. At this time, when the carbon dioxide concentration in the gas sent to the continuous furnace is compared with the carbon dioxide concentration in the gas exhausted from the continuous furnace, the carbon dioxide concentration in the gas exhausted from the continuous furnace is higher than the carbon dioxide concentration in the gas sent to the continuous furnace. Next, the mixture discharged from the continuous furnace is naturally cooled to room temperature, and the heated mixture is recovered.
[0158] In Example 1, the continuous furnace (heating space) has a high temperature region and a low temperature region, and the carbon dioxide concentration in the high temperature region is lower than that in the low temperature region, so that high temperature carbon dioxide is less likely to come into contact with the positive electrode active material. In addition, by feeding air in the continuous furnace in a direction perpendicular to the direction of movement of the mixture, it is possible to exhaust a part of the carbon dioxide generated by heating in the continuous furnace, and it is possible to prevent carbon dioxide from stagnation in the continuous furnace. As a result, it is possible to suppress the increase in the concentration and temperature of carbon dioxide generated in the continuous furnace, and it is possible to produce a recycled positive electrode active material while suppressing the deterioration of the positive electrode active material due to high temperature carbon dioxide.
Claims
1. A method for producing a recycled positive electrode active material, comprising: (1) A step of mixing a positive electrode mixture containing a positive electrode active material and a carbon-containing material with an activation treatment agent containing one or more alkali metal compounds to obtain a mixture; (2) heating the mixture in a heating space having a high-temperature region and a low-temperature region that is lower in temperature than the high-temperature region, and in which the carbon dioxide concentration in the high-temperature region is lower than the carbon dioxide concentration in the low-temperature region, to obtain a heated mixture; and (3) recovering the heated positive electrode active material from the heated mixture; Including, In the step (2), air is sent from the high temperature region to the low temperature region in the heating space.
2. A method for producing a recycled positive electrode active material, comprising the steps of: (1) A step of mixing a positive electrode mixture containing a positive electrode active material and a carbon-containing material with an activation treatment agent containing one or more alkali metal compounds to obtain a mixture; (2) heating the mixture in a heating space having a high-temperature region and a low-temperature region that is lower in temperature than the high-temperature region, and in which the carbon dioxide concentration in the high-temperature region is lower than the carbon dioxide concentration in the low-temperature region, to obtain a heated mixture; and (3) recovering the heated positive electrode active material from the heated mixture; Including, In the step (2), the mixture is heated to a temperature below the melting initiation temperature of the activation treatment agent.
3. The method according to claim 1 or 2, wherein the heating space is a continuous furnace.
4. The method according to claim 2 , wherein in the step (2), air is sent from the high temperature region to the low temperature region in the heating space.
5. 5. The manufacturing method according to claim 1, wherein in the step (2), when a carbon dioxide concentration in the gas fed into the heating space is compared with a carbon dioxide concentration in the gas exhausted from the heating space, the gas exhausted from the heating space has a higher carbon dioxide concentration.
6. The method according to claim 1 or 2, wherein carbon dioxide is separated or removed in the high temperature region of the step (2).
7. The method according to claim 1 , wherein in the step (2), the mixture is heated to a temperature equal to or higher than the melting point of the activation treatment agent.
8. The method according to claim 1 or 2, wherein the positive electrode active material comprises a lithium compound.
9. The manufacturing method according to claim 1 or 2, wherein the positive electrode active material comprises a composite oxide containing at least one element selected from the following element group 1 and at least one element selected from the following element group 2: Element group 1: Ni, Co, Mn, Fe, Al, and P Element group 2: Li, Na, K, Ca, Sr, Ba, and Mg
10. The method according to claim 1 or 2, wherein the activation treatment agent contains at least one compound selected from the group consisting of potassium compounds and sodium compounds.
Citation Information
Patent Citations
Method for recovering active material from discarded battery material
JP2012186150A
Production method of positive electrode active material for lithium ion secondary battery and heat treatment device
JP2019096422A
Positive electrode active material for lithium ion secondary battery, manufacturing method thereof, and lithium ion secondary battery
JP2021180088A